Discourse macrolinguistic impairment as a marker of linguistic and extralinguistic functions decline in early Alzheimer's disease. Issue 3 (15th November 2018) - Pistono, Aurélie; Jucla, M.; Bézy, C.; Lemesle, B.; Le Men, J.; Pariente, J.
Abstract: Background: Alzheimer's disease is characterized by macrolinguistic changes. This decline is often analyzed with quantitative scales. Aims: To analyze discourse production in early Alzheimer's disease (AD) and to identify qualitative markers of macrolinguistic decline. Methods & Procedures: We analyzed macrolinguistic features of a clinical narrative task along with patients' cognitive changes. To do so, 17 early AD participants and 17 healthy controls were recruited and given a full neuropsychological and language assessment. Narrative discourses produced during the language assessment were transcribed and macrolinguistic features were qualitatively analyzed (i.e., local and global coherence marks and discourse informativeness). Inter‐group comparison was complemented by intra‐group correlation. As some inter‐group comparisons revealed the existence of subgroups of patients, permutation tests were used to investigate how these subgroups differed vis‐à‐vis cognitive measures. Outcomes & Results: Overall, the results indicate that AD participants presented declines in informativeness and global coherence, correlated with declines in memory and executive functions. Permutation tests showed that participants with AD producing referential errors or misinterpretations had a deeper lexical–executive decline and a lower Mini‐Mental State Evaluation (MMSE). Conclusions & Implications: This study shows that two clinically relevant, qualitative signs differ in discourse production between typical ageing and early AD, namely information units and modalizing discourse. It also shows that macrolinguistic assessment is a useful tool for revealing impaired communication and cognition in early AD. Although lexical processing decline probably contributes to patients' macrolinguistic impairment, implications of extralinguistic functioning should be further investigated.